2016
DOI: 10.1016/j.cnsns.2015.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Steady state, oscillations and chaotic behavior of a gas inside a cylinder with a mobile piston controlled by PI and nonlinear control

Abstract: This paper analyzes the behavior of nitrogen inside a closed cylinder with a mobile piston actuated by a nonlinear spring, a viscous damper and a control force which compensates partially the effect of the high gas pressure. Two helical heating coils are The Melnikov method has been used to obtain sufficient conditions for chaotic behavior, which has also been investigated by means of the sensitive dependence, Lyapunov exponents and the power spectral density. The validity of the proposed model has been analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…w is an external harmonic disturbance applied to the piston. This issue has been investigated in (Pérez-Molina et al, 2016) but at low pressures (rather than with large pressure excursions), for which only the first and second virial coefficients provide helpful information. It should be remarked that the model equations remain unaltered with the change indicated in Eq (62), whereas the gas presents chaotic behavior for the values A F = 0.02, ω f = 5.2 rad/s and assuming that f p = 0 so that the friction it is not compensated by the control law (62).…”
Section: Analysis Of the Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…w is an external harmonic disturbance applied to the piston. This issue has been investigated in (Pérez-Molina et al, 2016) but at low pressures (rather than with large pressure excursions), for which only the first and second virial coefficients provide helpful information. It should be remarked that the model equations remain unaltered with the change indicated in Eq (62), whereas the gas presents chaotic behavior for the values A F = 0.02, ω f = 5.2 rad/s and assuming that f p = 0 so that the friction it is not compensated by the control law (62).…”
Section: Analysis Of the Resultsmentioning
confidence: 99%
“…For a given temperature, the results of Figs 11 and 12 can be used to investigate the pressure range within which a state equation can be compared with the HP state equation as a function of the number of virial coefficients. It should be recalled that the PI controller maintains the gas temperature almost constant (Albertos et al, 2004;Pérez-Molina et al, 2016), as shown in Figs 2 c), 4 c) and 8 b). In Figs 13 and 14…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations